Volunteering and the strategic value of ignorance - Florian Morath (Center for Economic Studies and ifo Institute (CESifo), 2011)
Private provision of public goods often takes place as a war of attrition: individuals wait until someone else volunteers and provides the good. After a certain time period, however, one individual may be randomly selected. If the individuals are uncertain about their cost of provision, but can find out about this cost ahead of the volunteering game, a strategic value is attached to the information, and individuals may prefer not to learn their cost of provision. If the time horizon is sufficiently short, in equilibrium only one individual may acquire information about his cost. For a long time horizon, acquiring information is strictly dominant. The time limit is an important instrument in influencing the efficiency of the volunteering game.
Keywords: H41; D44; D82; D83; 330; war of attrition; volunteering; discrete public goods; asymmetric information; information acquisition; Öffentliches Gut; Ehrenamtliche Arbeit; Asymmetrische Information; Informationsverhalten; Nichtkooperatives Spiel; Theorie